Experimental Models of Neuroimmunological Disorders: A Review - da Silva, Ana Paula Bornes; Silva, Rodrigo Braccini Madeira; Goi, Leise Daniele Sckenal; Molina, Rachel Dias; Machado, Denise Cantarelli; Sato, Douglas Kazutoshi (Frontiers in Neurology, 2020)
Immune-mediated inflammatory diseases of the central nervous system (CNS) are a group of neurological disorders in which inflammation and/or demyelination are induced by cellular and humoral immune responses specific to CNS antigens. They include diseases such as multiple sclerosis (MS), neuromyelitis optica spectrum disorders (NMOSD), acute disseminated encephalomyelitis (ADEM) and anti-NMDA receptor encephalitis (NMDAR encephalitis). Over the years, many in vivo and in vitro models were used to study clinical, pathological, physiological and immunological features of these neuroimmunological disorders. Nevertheless, there are important aspects of human diseases that are not fully reproduced in the experimental models due to their technical limitations. In this review, we describe the preclinical models of neuroimmune disorders, and how they contributed to the understanding of these disorders and explore potential treatments. We also describe the purpose and limitation of each one, as well as the recent advances in this field.